UV-Assisted Oxidative Cross-linking for the Efficient Manufacturing of Lignin-Derived Carbon Fibers - Sung-Soo Kim (한국고분자학회 2021년도 추계학술대회 연구논문 초록집 제46권 제2호, 2021)
Carbon fibers have garnered great interest from researchers due to their remarkable mechanical properties, while the growth of carbon fiber market has been limited by the high manufacturing cost. To address this issue, the utilization of low-cost carbon fiber precursors has been widely explored because the precursor is a major cost element. Lignin, which is hyperbranched phenolic polymer derived from lignocellulosic biomass, is a cost-effective precursor source suitable for the production of low-cost carbon fibers, since a large quantity of lignin are available as waste product of pulp/paper industries. In this presentation, synthesis of fatty-acid functionalized lignin precursors and their effective conversion to carbonized materials are introduced, where UV-triggered oxidative reactions prior to subsequent heat treatments played a pivotal role in the rapid thermostabilization process without melt deformation.